Distributional niche of relatively rare sable antelope in a South African savanna: habitat versus biotic relationships. Issue 1 (18th July 2012) - Chirima, George J.; Owen‐Smith, Norman; Erasmus, Barend F. N.; Parrini, Francesca
Abstract : The geographic distribution of a species is governed by climatic conditions, topography, resources and habitat structure determining the fundamental niche, while the local distribution expressed via home range occupation may be compressed by biotic interactions with competitors and predators, restricting the realised niche. Biotic influences could be especially important for relatively rare species. We investigated how rainfall, geology, land type and abundance of other ungulate species serving as competitors or prey for predators contributed to the patchy distribution of sable antelope herds within Kruger National Park. Data were provided by annual aerial surveys of ungulate populations conducted between 1978 and 1988. Sable herds were more commonly present on granitic and sandstone substrates than on more fertile basalt. They occurred both in the moist south‐west and dry north of the park. They were most abundant in sour bushveld and mopane savanna woodland, and mostly absent from knob thorn‐marula parkland. The presence of sable was negatively associated with high concentrations of impala and wildebeest, less consistently related to the abundance of zebra, and positively associated with the occurrence of buffalo herds. Best supported models included the separate effects of the most abundant grazers along with land type. Interspecific relationships seemed more consistent with vulnerability to predation as the underlying mechanism restricting the distribution of sable herds than with competitive displacement. Sable favoured land types distinct from those where wildebeest, the most preferred prey of lions, and impala, numerically the most important resident prey species, were most abundant. Hence the risk of predation, associated with habitat conditions where abundant prey species are most concentrated, can exert an overriding influence on the distribution of rarer species in terms of their home range occupation.